Appearance/Image- and Performance-Enhancing Drug Users: A Forensic Approach. (December 2018) - Lusetti, Monia; Licata, Manuela; Silingardi, Enrico; Bonsignore, Alessandro; Palmiere, Cristian
Abstract : Abstract: Image- and performance-enhancing drugs include a wide range of substances used to promote physical changes to enhance appearance. Anabolic androgen steroids are the most widely used image- and performance-enhancing drugs along with a wide variety of additional substances. The aim of this study was to identify the pathological changes pertaining to the cardiovascular system possibly involved in the death and characterize the substances associated with steroid use and their possible role in the death. A series of deaths involving image- and performance-enhancing drug users were selected. Nandrolone and testosterone were the most frequently identified steroids. The most commonly illegal drugs found were tetrahydrocannabinol, cocaine, and methadone. Antidepressants, opioids, benzodiazepines, and barbiturates were also found. These findings highlight that results obtained from postmortem investigations should be meticulously evaluated to understand the weight that each identified substance may have played in the death process and exclude any alternative causes of death.